ANALYSIS OF THE DATA SOURCES FOR SIZING THE PHENOMENON OF INTERNATIONAL MIGRATION IN THE CONTEXT OF THE MAJOR EXODUS OF ROMANIAN LABOR FORCE - Gabriela PRELIPCEAN; Paul-Panfil IVAN (Eastern European Journal of Regional Studies, 2023)
Being a complex and multi-criteria phenomenon, the international migration can have a lot of different meanings, which suppose different scopes and methods of estimating various data, depending on the hypotheses and research objectives pursued. In the last decade the mass-media also gave an increased importance to the phenomenon and in the era of fake news, it led to the fact that the magnitude of the phenomenon was often communicated differently from the real situation or the existing statistics. Even though there is a great diversity of data sources that could be used to estimate international migration flows, these are not directly oriented to measure migration, so great difficulties in terms of data comparability occur very often. In Romania the phenomenon of international migration has taken a large scale, the country being on the first places worldwide in terms of labor force exits to destination countries, but, practically, the Romanian authorities have very less information regarding the residence of Romanian citizens abroad and, implicitly, no data is collected regarding the real volume of the migration phenomenon. This paper aims to inventory the available data sources regarding international migration from Romania and, as much as possible, to propose solutions by which this phenomenon could be better quantified to support the development of effective migration policies. The research methodology consists in the theoretical analysis of data sources and indicators that measure the migration phenomenon in order to identify a possibility to quantify the volume of the migrant population by proposing a model that calculates the potential migrant workforce calculated as a difference between the labor resource and the employed population.